Resistivity Survey for Slope Zonation in Landslide Risk Study - Wahab W.A.; Omar R.C.; Taher T.M.; Roslan R.; Baharuddin I.N.Z.; Khalid N.H.N.; Isa A.A.M.; Zarime N.A.; Solemon B.; Jaapar A.R. (Springer Science and Business Media Deutschland GmbH, 2024)
The resistivity and seismic methods were employed for slope risk investigation at Tower 42, Jor Bintang transmission line in Cameron Highlands, Pahang, with the aim of facilitating slope maintenance. The areaaround the tower legs displayed several propertiesthat hinted at potential slope stability issues. To identify the optimal test line for geophysical testing, a novel approach was applied utilizing the slope risk assessment method, thereby determining the criticality of the sub-divided slopes. The selection of the geophysical test line was based on geological and geotechnical properties, with Line 1 covering a total length of 100 m from the top of the front berm to the top of the back berm, and Line 2 crossing Line 1, spanning 120 m. The resistivity and seismic methods yielded positive results, with the 2D-generated resistivity images indicating the presence of weathered bedrock beneath the utilized test lines. Based on these findings, it is recommended that researchers consider employing this method as a pre-assessment in slope investigations. This approach significantly aids in determining the most suitable location for conducting a slope survey, ensuring the accuracy of the obtained results. The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2023.